Synthesis, structure and bonding in pentagonal bipyramidal cluster compounds containing a cyclo-Sn5 ring, [(CO)3MSn5M(CO)3]4− (M = Cr, Mo) - Mondal, S; Chen, W-X; Sun, Z-M; McGrady, JE (MDPI, 2022)
In this paper, we report the synthesis and structural characterisation of two hetero-metallic clusters, [(CO)3CrSn5Cr(CO)3]4− and [(CO)3MoSn5Mo(CO)3]4−, both of which have a pentagonal bipyramidal core. The structures are similar to that of previously reported [(CO)3MoPb5Mo(CO)3]4− and our analysis of the bonding suggests that they are best formulated as containing Sn54− rings bridging two zerovalent M(CO)3 fragments. The electronic structure is compared to two isolobal M2E5 clusters, [CpCrP5CrCp]− and Tl77−, both of which show clear evidence for trans-annular bonds between the apical atoms that is not immediately obvious in the title clusters. Our analysis shows that the balance between E-E and M-M bonding is a delicate one, and shifts in the relative energies of the orbitals on the E5 and M2 fragments generate a continuum of bonding situations linked by the degree of localisation of the cluster LUMO.